STRATEGI PENYULUHAN DAN PELATIHAN BAGI SISWA SMK: “MEMBANGUN JIWA ENTREPRENEUR MELALUI PEMASARAN ONLINE DALAM ERA MAKING INDONESIA 4.0" - Sujatini, Siti; Budilaksono, Sularso; Puspita Dewi, Euis; Malays Sari Sakti, Essy; Pramestari, Diah; Dinariana, Dwi; Suryani, Fitri; Henni, Henni (Jurnal Abdi Insani, 2024)
The entrepreneurship ratio is an indicator of a country's progress, currently Indonesia's entrepreneurship ratio is still low. Vocational education, especially at Vocational High Schools (SMK), has a crucial role in preparing the young generation to face the dynamics of industry 4.0 in Indonesia. This article aims to explain a community service approach that is focused on strengthening the entrepreneurial spirit of vocational school students through socialization and training strategies, especially in the context of online marketing. By utilizing the potential of digital technology, this activity is designed to increase students' understanding of the essence of entrepreneurship in the digital era to identify business opportunities and adapt to a rapidly changing economic environment. This article also links this initiative to the Making Indonesia 4.0 vision, which highlights the importance of mastering technology and creativity in driving sustainable economic growth. The implementation of this strategy is expected to make a significant contribution in preparing Indonesia's young generation to become strong economic actors in the industrial era 4.0.  The method of this activity is counseling and training, starting from preparing Extension Materials, Identifying Participants, Implementing Counseling, Training Workshops, Mentoring and Mentoring, Evaluation and Feedback. The results of this activity show that students basically already know the basic meaning of websites and Google sites, but do not yet understand how to access them, how to use websites, what are the advantages of using websites, etc. in more detail. . After this training and counseling, students (activity participants) can understand clearly. As for suggestions from the writing team, considering the large enthusiasm of the participants for this activity, activities like this need to be implemented in vocational schools and similar areas in other areas in Jabodetabek